Intelligent Ventilation Systems in Mining Engineering: Is ZigBee WSN Technology the Best Choice? - Mario Di Nardo; Haoxuan Yu (Applied System Innovation, 2021)
With the continuous development and progress of the mining industry, various technologies in mining engineering have gradually developed towards the intelligent stage, and the ventilation system is no exception. Since ancient times, mine ventilation has been a necessary part of mining engineering, and so the optimization of mine ventilation undoubtedly plays a great role in mining production. This two-part opinion paper briefly introduces the development of the intelligent ventilation in mining engineering and serves as a guide to the Tossing out a brick to get a jade gem, with implications for both the development and the future of the underground mine ventilation systems. Finally, in the second part of the paper, we explain why we think ZigBee WSN technology is the best choice in intelligent ventilation systems in underground mines at the present stage.